MicroRNA 223 Targeting ATG16L1 Affects Microglial Autophagy in the Kainic Acid Model of Temporal Lobe Epilepsy - He, Zhuoyi; Chen, Houminji; Zhong, Yongsheng; Yang, Qihang; Wang, Xuemin; Chen, Rongqing; Guo, Yanwu (Frontiers in Neurology, 2021)
This study aimed to explore whether microRNA (miR) 223 affects microglial autophagy by targeting autophagy-related 16-like 1 (ATG16L1) in the kainic acid (KA) model of temporal lobe epilepsy (TLE). The miRNA and mRNA expression levels were quantified using quantitative real-time polymerase chain reaction (qRT-PCR), and the protein expression was investigated using western blotting. A dual-luciferase reporter assay was used to test the direct interaction between miR 223 and ATG16L1. In situ hybridization was performed to measure the hippocampal expression of miR 223. We used immunofluorescence staining to assess the expression of ATG16L1 and microtubule-associated protein light chain 3 (LC3) in the murine hippocampal microglia. Inhibitor of miR 223 was utilized to investigate the role of miR 223 in TLE, and the epileptic activity was assessed using electroencephalography (EEG). The autophagosomes were observed by transmission electron microscopy. In patients with TLE, the murine KA model of TLE, and the KA-stimulated BV2 cells, miR 223 and sequestosome 1(SQSTM1/P62) expressions were remarkably increased, whereas ATG16L1 and LC3 levels were significantly decreased. Using a dual-luciferase reporter assay, ATG16L1 was determined as a direct target of miR 223. Treatment with antagomir 223 alleviated epilepsy, prevented abnormalities in electroencephalography recordings and increased the ATG16L1 and LC3 levels in KA-treated mice. Inhibition of miR 223 induced increased autophagy in BV2 cells upon Rapamycin stimulation. These findings show that miR 223 affects microglial autophagy via ATG16L1 in the KA model of TLE. The miR 223/ATG16L1 pathway may offer a new treatment option for TLE.